2021
DOI: 10.1080/08897077.2021.1915916
|View full text |Cite
|
Sign up to set email alerts
|

What Parents of Adolescents in Residential Substance Use Treatment Want from Continuing Care: A Content Analysis of Online Forum Posts

Abstract: Background Parents of adolescents in residential substance use (SU) treatment face a myriad of barriers to continuing care services. Growing research suggests that mobile health (mHealth) technologies can overcome common barriers to continuing care services, yet no work has addressed parents’ needs. To gain insight into parents’ continuing care needs, we analyzed online forum posts made by parents who received a novel mHealth intervention. Methods Thirty parents received access to an online networking forum wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 67 publications
1
4
0
Order By: Relevance
“…This study aimed to elicit the needs of parents who did not receive continuing care in the critical period after their teen's discharge from residential treatment. Three of the six major themes identified in the current study (parenting skills, parent support, adolescent substance use) were consistent with a priori major themes identified in our team's examination of posts to an online forum made by parents receiving an active continuing care intervention ( Helseth et al., 2021 ). These identified themes reflected informational needs about the adolescent's substance use, as well as requests for concrete skills and support to navigate the post-discharge period.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…This study aimed to elicit the needs of parents who did not receive continuing care in the critical period after their teen's discharge from residential treatment. Three of the six major themes identified in the current study (parenting skills, parent support, adolescent substance use) were consistent with a priori major themes identified in our team's examination of posts to an online forum made by parents receiving an active continuing care intervention ( Helseth et al., 2021 ). These identified themes reflected informational needs about the adolescent's substance use, as well as requests for concrete skills and support to navigate the post-discharge period.…”
Section: Discussionsupporting
confidence: 73%
“…We subsequently used our formative research to design and pilot a technology-assisted intervention with 30 parents of adolescents in residential treatment for substance use that allowed parents to network in two forums: one in which they could ask a clinical expert questions and one in which they could interact with other parents ( Becker, Helseth, Janssen, Kelly, Escobar, & Spirito, 2021 ; Becker, Helseth, Janssen, Kelly, Escobar, Souza, et al, 2021 ). A content analysis of posts from parents who received this technology-assisted intervention revealed that parent questions and comments clustered around five major themes: parenting skills; parent support; managing the post-discharge transition; adolescent substance use; family functioning ( Helseth et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…During hospitalization and discharge, only relying on health education of discharged patients with T-tube by medical staff cannot improve their mastery of T-tube management and nursing knowledge, thus affecting the prognosis of patients [ 21 , 22 ]. The continuous nursing mode based on mobile Internet can ensure real-time communication between medical staff and patients; strengthen medical staff's grasp of patients' psychological problems, health management, and rehabilitation effect evaluation; and improve patients' trust in medical staff and patients' nursing satisfaction [ 23 ]. This nursing model can mobilize the subjective initiative of patients and their families, improve the self-care ability of patients and their families, and reduce the incidence of complications and referral rate in the nursing process [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the pilot trial, 21 of the 30 parents (70%) randomized to Parent SMART posted a total of 16 times in Ask an Expert and 50 times in Connect with Parents. Qualitative analysis of the posts revealed five key themes: parenting skills, parent support, managing the transition home from residential care, adolescent substance use, and family functioning [ 34 ]. Parents will be told to expect replies within 24 hours; the average lag time in our pilot trial was 1 to 2 hours.…”
Section: Methodsmentioning
confidence: 99%